(untitled) (Research, Society and Development, 2022)
The increase in demand for water use has caused serious environmental problems and conflicts between users. Reservoirs off-stream the water bed, commonly called “Piscinões”, have been presented as a common practice for maintaining irrigated agriculture in the dry season. During the rainy season and the beginning of the dry season, the user of water resources captures more water than he needs in order to store the water resources and use them in the period of lower flows in the rivers. For a more efficient management of the safety of these hydraulic structures, it is important to know the real impact that the current pond-reservoirs can cause to the environment and the people who live in their surroundings. Inserted in this context, methods, methodologies and tools capable of measuring the value of risk through indicators were found in the technical literature and the Potential Environmental Damage methodology was adopted. The present work adopted the Potential Risk methodology proposed by COGERH and the Potential Environmental Damage proposed by FEAM. It is concluded that the tools can be adopted for a classification of reservoirs-pools, however there is room for improvement and an improvement in the management of these water structures.